I keep reading that linear returns aggregate across securities, but I'm having trouble proving it. I suspect there's some mistake in my approach; I'd appreciate some help in seeing it.

Suppose we have two securities, $A$ and $B$. They have prices at timestep $t$ of $P_A^t$ and $P_B^t$, respectively. The portfolio has weights $w_A$ and $w_B$, which sum to 1. The price of the portfolio is then

$$P_P^t = w_A P_A^t + w_B P_B^t.$$

We define linear returns via the formula

$$R^t = \frac{P^t}{P^{t-1}} - 1.$$

Thus, the linear returns of the portfolio are

$$R_P^t = \frac{P_P^t}{P_P^{t-1}} - 1 = \frac{w_A P_A^t + w_B P_B^t}{w_A P_A^{t-1} + w_B P_B^{t-1}} - 1$$

I see it claimed in various locations around the internet that these returns aggregate over securities, which is to say that

$$R_P^t = w_A R_A^t + w_B R_B^t.$$

However, this formula yields

$$ R_P^t = w_A \frac{P_A^t}{P_A^{t-1}} + w_B \frac{P_B^t}{P_B^{t-1}} - 1$$

which, as far as I can see, is not in general equal to the previous expression for returns. In particular,

$$ w_A \frac{P_A^t}{P_A^{t-1}} + w_B \frac{P_B^t}{P_B^{t-1}} \neq \frac{w_A P_A^t + w_B P_B^t}{w_A P_A^{t-1} + w_B P_B^{t-1}}.$$

What am I missing here? I need to be able to use linearity when justifying Markowitz-style optimization.


1 Answer 1


I think you are simply confusing percentage weights and number of assets.

In your definition the initial percentage weight of the $m$ assets in the portfolio are given by $w_i^{t - 1}$ and they sum to one, i.e.

\begin{equation} \sum_{i = 1}^m w_i^{t - 1} = 1. \end{equation}

Now define the absolute number of assets as $n_i$. They are linked to the percentage weights through

\begin{equation} w_i^{t - 1} = \frac{n_i P_i^{t - 1}}{\sum_{j = 1}^m n_j P_j^{t - 1}}. \end{equation}

As you don't rebalance your portfolio, the number of assets stays the same in $t - 1$ and $t$. The value of the portfolio at any time $t$ is

\begin{equation} P_P^t = \sum_{i = 1}^m n_i P_i^t. \end{equation}


\begin{eqnarray} R_P^t & = & \frac{P_P^t}{P_P^{t - 1}} - 1\\ & = & \frac{\sum_{i = 1}^m n_i P_i^t}{\sum_{j = 1}^m n_j P_j^{t - 1}} - 1\\ & = & \sum_{i = 1}^m \left( \frac{n_i P_i^{t - 1}}{\sum_{j = 1}^m n_j P_j^{t - 1}} \right)\frac{P_i^t}{P_i^{t - 1}} - 1\\ & = & \sum_{i = 1}^m w_i^{t - 1} \frac{P_i^t}{P_i^{t - 1}} - 1\\ & = & \sum_{i = 1}^m w_i^{t - 1} R_i^t \end{eqnarray}

Note that generally $w_i^t \neq w_i^{t - 1}$.

  • 2
    $\begingroup$ In simple terms the $n_i$ would be for example the number of shares of stock, e.g. you have 100 shares of MSFT and 200 shares of XOM... or whatever. $\endgroup$
    – nbbo2
    Jan 18, 2017 at 23:39
  • $\begingroup$ This is helpful. Another way that I have thought about it is that rather than using price $P_t$, I use a scaled value $V_t$ where $V_0=1$ by definition. $\endgroup$ Jan 21, 2017 at 20:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.